Temporal hemodynamic classification of two hands tapping using functional near—infrared spectroscopy - Nguyen, Hai T.; Ngo, Cuong Q.; Truong Quang Dang, KHOA; Vo, Van Toi (Frontiers in Human Neuroscience, 2013)
In recent decades, a lot of achievements have been obtained in imaging and cognitive neuroscience of human brain. Brain’s activities can be shown by a number of different kinds of non-invasive technologies, such as: Near-Infrared Spectroscopy (NIRS), Magnetic Resonance Imaging (MRI) and ElectroEncephaloGraphy (EEG) (Wolpaw et al., 2002;Weiskopf et al., 2004;Blankertz et al., 2006). NIRS has become the convenient technology for experimental brain purposes. The change of oxygenation changes (oxy-Hb) along task period depending on location of channel on the cortex has been studied: sustained activation in the motor cortex, transient activation during the initial segments in the somatosensory cortex, and accumulating activation in the frontal lobe (Gentili et al., 2010). Oxy-Hb concentration at the aforementioned sites in the brain can also be used as a predictive factor allows prediction of subject’s investigation behavior with a considerable degree of precision (Shimokawa et al., 2009). In this paper, a study of recognition algorithm will be described for recognition whether one taps the left hand or the right hand. Data with noises and artifacts collected from a multi-channel system will be pre-processed using a Savitzky- Golay filter for getting more smoothly data. Characteristics of the filtered signals during left and right hand tapping process will be extracted using a polynomial regression algorithm. Coefficients of the polynomial, which correspond to Oxygen-Hemoglobin (Oxy- Hb) concentration, will be applied for the recognition models of hand tapping. Support Vector Machines (SVM) will be applied to validate the obtained coefficient data for hand tapping recognition. In addition, for the objective of comparison, Artificial Neural Networks (ANNs) was also applied to recognize hand tapping side with the same principle. Experimental results have been done many trials on three subjects to illustrate the effectiveness of the proposed method.